RETAIL SALES INDEX, PRICE EXPECTATION INDEX AND SALES EXPECTATION INDEX IN LHOKSEUMAWE CITY - Rahmaniar; Amru Usman; Rusydi; M. Subhan; T. Edyansyah (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
The objective of this research is to support Bank Indonesia (BI) in updating the Retail Sales Survey (SPE) data, which is a routine monthly survey conducted by Bank Indonesia as a prompt indicator of household consumption (consumption spending). The method used in this study is the community empowerment method, based on commodity coverage, since 2012 SPE grouping has been carried out through the Indonesian Business Field Standard Classification (KBLI) approach, namely spare parts & accessories, food, beverages & tobacco, motor vehicle fuel, equipment information & communication, other household goods, cultural & recreational goods and Other Goods. Sampling was carried out purposively by considering the respondent's criteria,